2022
DOI: 10.1039/d1cp04848a
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to fluorescence via restriction of intramolecular motion in substituted tetraphenylethylenes

Abstract: The design of materials with enhanced luminescence properties is a fast-developing field due to the potential applicability of these materials as light-emitting diodes or for bioimaging. A transparent way to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 69 publications
1
8
0
Order By: Relevance
“…53,55,60 However, very recent theoretical calculations have predicted that bulky substituents in the phenyl rings might affect the formation of CRS slowing the process down to ∼750 fs. 71 In our studies, we observed a second fs-component of ∼600 fs that decays at the blue side of the observation range (Family II) and rises at the red one (Family III). The value of this component agrees well with the predicted one for the formation of CRS for substituted TPE, and thus we assign it to this process (Scheme 1).…”
Section: Resultssupporting
confidence: 50%
See 2 more Smart Citations
“…53,55,60 However, very recent theoretical calculations have predicted that bulky substituents in the phenyl rings might affect the formation of CRS slowing the process down to ∼750 fs. 71 In our studies, we observed a second fs-component of ∼600 fs that decays at the blue side of the observation range (Family II) and rises at the red one (Family III). The value of this component agrees well with the predicted one for the formation of CRS for substituted TPE, and thus we assign it to this process (Scheme 1).…”
Section: Resultssupporting
confidence: 50%
“…A recent theoretical study has predicted that the presence of bulky substituents in the phenyl rings of TPE can significantly affect these torsional angles with respect to the unsubstituted TPE. 71 We assign the two shorter components (t 1 = 170 ps and t 2 = 470 ps), observed at the blue part of the emission spectrum, to the partially relaxed structures having different conformations of the phenyl groups and having experienced an ultrafast charge redistribution giving rise to different emission lifetimes. They may undergo a twisting motion producing green-red emitting species.…”
Section: Picosecond Time-resolved Emission Observationmentioning
confidence: 88%
See 1 more Smart Citation
“…The SLE characteristics of TPE/HPS derivatives in the condensed phase mainly originate from the torsional twist and rigidity of their p-framework, 41,42 which mainly govern their emission intensity but have limited influence on wavelength tuning. Hence, SLE-active NIR luminogens have been developed by incorporating donor/acceptor units into the TPE pskeleton because ultra-strong electron-acceptors such as benzobisthiadiazole (BBT) and thiadiazoloquinoxaline (TQ) units are known for pushing the spectral region toward the NIR window through LUMO stabilization.…”
Section: Sriram Kanvahmentioning
confidence: 99%
“…17,18 Free intramolecular motion can be restricted in aggregates due to intermolecular interaction, thus resulting in bright fluorescence. 19 In RACl, 16 an excited AIEgen can decay to the ground state via an energetically available conical intersection in solution, which leads to weak or non-fluorescence. However, due to the steric hindrance effect in aggregates, the energy barrier of accessing the conical intersection increases sharply, and the AIEgen recovers its bright emission.…”
Section: Introductionmentioning
confidence: 99%